Plectin ensures intestinal epithelial integrity and protects colon against colitis - Krausova, Alzbeta; Buresova, Petra; Sarnova, Lenka; Oyman-Eyrilmez, Gizem; Skarda, Jozef; Wohl, Pavel; Bajer, Lukas; Sticova, Eva; Bartonova, Lenka; Pacha, Jiri; Koubkova, Gizela; Prochazka, Jan; et al. (Mucosal immunology, 2021)
Plectin, a highly versatile cytolinker protein, provides tissues with mechanical stability through the integration of intermediate filaments (IFs) with cell junctions. Here, we hypothesize that plectin-controlled cytoarchitecture is a critical determinant of the intestinal barrier function and homeostasis. Mice lacking plectin in an intestinal epithelial cell (IEC; PleΔIEC) spontaneously developed colitis characterized by extensive detachment of IECs from the basement membrane (BM), increased intestinal permeability, and inflammatory lesions. Moreover, plectin expression was reduced in the colons of ulcerative colitis (UC) patients and negatively correlated with the severity of colitis. Mechanistically, plectin deficiency in IECs led to aberrant keratin filament (KF) network organization and the formation of dysfunctional hemidesmosomes (HDs) and intercellular junctions. In addition, the hemidesmosomal α6β4 integrin (Itg) receptor showed attenuated association with KFs, and protein profiling revealed prominent downregulation of junctional constituents. Consistent with the effects of plectin loss in the intestinal epithelium, plectin-deficient IECs exhibited remarkably reduced mechanical stability and limited adhesion capacity in vitro. Feeding mice with a low-residue liquid diet that reduced mechanical stress and antibiotic treatment successfully mitigated epithelial damage in the PleΔIEC colon.